HPV and co-infections: impacts on semen inflammation, oxidative stress, and sperm quality - Olivera, Carolina; Paira, Daniela A.; Olmedo, Andres; Olmedo, Jose J.; Tissera, Andrea D.; Molina, Rosa I.; Ferreyra, Fernando N.; Martinez, Maria S.; Chocobar, Yair A.; Cuffini, Cecilia G.; Motrich, Ruben D.; Rivero, Virginia E. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHuman papillomavirus (HPV) is the most common sexually transmitted viral infection worldwide, which has been suggested to induce male urogenital inflammation and affect fertility. However, reported evidence is scarce and inconclusive. Moreover, the putative effects of coinfections remain largely unexplored. This study aimed to analyze HPV male urogenital infection, both as a single infection and in conjunction with other common uropathogens, along with its impact on inflammatory biomarkers in semen, oxidative stress and sperm quality.MethodsThe prevalence of HPV urogenital infection and its coinfection with several other uropathogens was analyzed in a cohort of 205 men attending a urology clinic. Furthermore, levels of sperm leukocyte subsets and inflammatory cytokines, semen analysis, sperm apoptosis and necrosis, and sperm ROS production were assessed.ResultsA considerable prevalence (19%) of HPV male urogenital infection was found. Interestingly, HPV was detected coinfecting with at least one other uropathogen in most cases (74.4%). Notably, the most frequently detected coinfection was C. trachomatis (CT, 52% of cases). Remarkably, patients solely infected with HPV showed no significant alterations in conventional sperm quality parameters as well as reduced concentrations of IL-6 and leukocytes in semen. However, patients coinfected with HPV and CT showed significantly impaired sperm concentration and motility and increased levels of IL-6 in semen.ConclusionThese results indicate that HPV infection alone does not associate with semen inflammation or major changes in sperm quality. However, co-infection with CT is associated with both semen inflammation and reduced sperm quality. This indicates that, besides being prevalent, concurrent HPV and CT infections in semen may represent a unique clinical entity with particular characteristics.